Spontaneous Intramuscular Hemorrhage in Anti-MDA5 Positive Dermatomyositis: A Case Series and Literature Review - Xu, Zhangling; Lv, Xia; Xu, Wenwen; Ye, Yan; Wang, Xiaodong; Ye, Shuang; Ding, Huihua; Wu, Wanlong (Frontiers in Medicine, 2022)
Objective Spontaneous intramuscular hemorrhage (SIH) is a rare but life-threatening complication associated with dermatomyositis (DM). This study reported a case series of SIH associated with DM. In addition, the characteristics and prognostic effects for this complication were analyzed based on literature review. Methods We reported seven cases of anti-melanoma differentiation-associated gene five positive dermatomyositis (MDA5+DM) complicated by SIH in our single-center cohort, and a comprehensive literature review was performed. Clinical characteristics, treatment, and outcome data of all eligible reported cases were summarized. Potential prognostic effects were identified by comparisons between the deceased and survivors. Results Among cumulatively reported patients with DM patients and SIH, the overall mortality was 60.9% (14/23) (including our cases). Fourteen out of nineteen (73.7%) hemorrhagic events occurred within 6 months of disease onset. Anti-MDA5 antibody predominated in those myositis-specific antibodies available cases (8/10), although patients with positive anti-NXP2 and anti-Mi2 have also been documented. Iliopsoas (52.2%, 12/23) was the most frequently involved bleeding location. Bleeding in deep muscles was identified to be associated with poorer prognosis. The mortality of patients with DM and deep muscular hematoma (non-palpable) (80%, 12/15) was significantly higher than that of patients with only superficial muscular hematoma (palpable) (25%, 2/8) (p =0.023). Conclusion Spontaneous hematoma in non-palpable deep muscles probably leads to excess mortality in dermatomyositis, particularly for those with anti-MDA5 antibody, which often occurs within 6 months of disease onset. Clinicians should be vigilant to this rare but potentially fatal complication and carefully balance the risks and benefits of prophylactic anti-thrombotic treatment.